Nonlinear Influence of Sound on the Vibrational Energy of Molecules in a Relaxing Gas - PERELOMOVA, Anna (Archives of Acoustics, 2012)
Dynamics of a weakly nonlinear and weakly dispersive flow of a gas where molecular vibrationalrelaxation takes place is studied. Variations in the vibrational energy in the field of intense sound isconsidered. These variations are caused by a nonlinear transfer of the acoustic energy into energy ofvibrational degrees of freedom in a relaxing gas. The final dynamic equation which describes this isinstantaneous, it includes a quadratic nonlinear acoustic source reflecting the nonlinear character ofinteraction of high-frequency acoustic and non-acoustic motions in a gas. All types of sound, periodic oraperiodic, may serve as an acoustic source. Some conclusions about temporal behavior of the vibrationalmode caused by periodic and aperiodic sounds are made.